2013
DOI: 10.1073/pnas.1316895110
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of closed head traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a substantial health issue worldwide, yet the mechanisms responsible for its complex spectrum of pathologies remains largely unknown. To investigate the mechanisms underlying TBI pathologies, we developed a model of TBI in Drosophila melanogaster. The model allows us to take advantage of the wealth of experimental tools available in flies. Closed head TBI was inflicted with a mechanical device that subjects flies to rapid acceleration and deceleration. Similar to humans with TBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
243
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(281 citation statements)
references
References 41 publications
32
243
5
1
Order By: Relevance
“…Flies subjected to strikes from the HIT device were incubated at 25°C in a vial with fly food, and the number of dead flies was counted after 24 hr. We used this approach to identify factors that affect the MI 24 and found that the MI 24 is not affected by the number of flies in a vial (10 to 60 flies was tested), the time between repetitive strikes (1 to 60 min was tested), or the sex of the fly 10 . In contrast, we found that age at the time of the primary injury and genotype did affect the MI 24 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Flies subjected to strikes from the HIT device were incubated at 25°C in a vial with fly food, and the number of dead flies was counted after 24 hr. We used this approach to identify factors that affect the MI 24 and found that the MI 24 is not affected by the number of flies in a vial (10 to 60 flies was tested), the time between repetitive strikes (1 to 60 min was tested), or the sex of the fly 10 . In contrast, we found that age at the time of the primary injury and genotype did affect the MI 24 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…To some extent, all contacts are likely to cause the fly brain to ricochet and deform against the head capsule, similar to what happens to humans in falls and car crashes 9 . Accordingly, flies treated with the HIT device display phenotypes consistent with brain injury, including temporary incapacitation followed by ataxia, gradual recovery of mobility, gene expression changes in the head, and progressive neurodegeneration in the brain 10 . Thus, the HIT device makes it possible to study TBI using the enormous arsenal of experimental tools and techniques developed for flies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 This work builds upon our prior publications that describe the development and initial characterization of a fly TBI model that uses a spring-loaded device to inflict closed-head TBI in adult flies. 39,40 We found that one of the consequences of TBI is death within 24 hrs of the initial injury and that genotype plays a major role in determining the percentage of flies that die within 24 hrs, which we call the mortality index at 24 hrs (MI 24 ). 38 Through Genome-wide association study (GWAS) analysis of many wild-type fly lines, we identified single-nucleotide polymorphisms (SNPs) in three epithelial barrier-related genes, big bang (bbg), scribble (scrib), and grainyhead (grh), as being significantly associated with the MI 24 .…”
Section: Tbi Increases Intestinal Permeability In Fliesmentioning
confidence: 99%